Construção/reconstrução de objeto de discurso : um estudo comparativo sobre construção de imagem pública em reportagens das revistas Veja e Carta Capital - Sousa, Bharbara Bonelle de (2018)
At the end of 2015 and during the year 2016, the Brazilian political framework underwent an extraordinary reconfiguration. The presidential representative, Dilma Rousseff, was charged with a crime of responsibility for administrative impropriety, prompting parliament to initiate impeachment proceedings. Some Brazilian magazines accompanied all the unfolding of this process and, by means of reports, presented different views in regarding the fact. It is noticed that, despite the assumption of the exemption, it is observed a critical posture of the reporters in the transmitted information, once each magazine constructs its position subjectively, with a certain point of view in order to meet its target. In this perspective, based on a qualitative and interpretative bias of reports published in the weekly magazines Veja and Carta Capital, this research aims to analyze the process of referentiation, in its course of categorization and recategorization, with the purpose of verifying how the object of discourse "Dilma Rousseff "is materialized in the reports of the two different magazines, as well as verify how the social image of the president is constructed and deconstructed discursively through the referential expressions. It is assumed that this construction is placed between two polar axes of different positions. To that end, as regards the theoretical contribution, it willbe mainly related to the theories of Mondada and Dubois (2015,1016), Marcuschi (2004, 2008, 2010), Koch (1998, 2005, 2011), Koch and Elias (2012, 2015), Cavalcante (2011, 2014) and Cortez (2013) regarding referentiation studies. In order to understand questions related to the social image, we have as contribution, the pragmatictheories that develop this theme from the notion of face and linguistic politeness, being of fundamental relevance the studies of authors like Goffman (1967,1980, 2011) and Brown & Levinson (1975).